Surgical Services in Bangladesh: Glorious 50 years for Bangladesh College of Physicians and Surgeons (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not availableJ Bangladesh Coll Phys Surg 2022; 40: 3